Hydrological Effects of the Planned Power Project and Protection of the Natura 2000 Areas: A Case Study of the Adamów Power Plant - Tomasz Kałuża; Ireneusz Laks; Jolanta Kanclerz; Ewelina Janicka-Kubiak; Mateusz Hämmerling; Stanisław Zaborowski (Energies, 2025)
The planned construction of a steam–gas unit at the Adamów Power Plant raises questions about the potential hydrological impact on the neighboring Natura 2000 protected areas, particularly the Middle Warta Valley (PLB300002) and the Jeziorsko Reservoir (PLB100002). These ecosystems play a key role in protecting bird habitats and biodiversity, and any changes in water management can affect their condition. This paper presents a detailed hydrological analysis of the Warta River and Jeziorsko Reservoir for 2018–2022, with a focus on low-flow periods. The Peak Over Threshold (POT) method and Q70% threshold were used to identify the frequency, length, and seasonality of low-flow periods in three water gauge profiles: Uniejów, Koło, and Sławsk. The longest recorded low-flow episode lasted 167 days. The permissible water intake for the investment (up to 0.8 m3∙s–1) is in accordance with the applicable permits and is used mainly for cooling purposes. Calculations indicate that under maximum intake conditions, the water level reduction in the Jeziorsko Reservoir would be between 1.7 and 2.0 mm∙day–1, depending on the current level of filling. Such changes do not disrupt the natural functions of the reservoir under typical conditions, although during prolonged droughts, they can pose a threat to protected areas. An analysis of the impact of periodic water overflow into the Kiełbaska Duża River indicates its negligible effect on water levels in the reservoir and flows in the Warta River. The results underscore the need for the integrated management of water and power resources, considering the increasing variability in hydrological conditions. Ensuring a balance between industrial needs and environmental protection is key to minimizing the potential impact of investments and implementing sustainable development principles.